Recent trends of extremophiles application in microbial electrochemical systems as energy scavenger: a mini review - S., Rana; P., Mishra; S., Krishnan; Zularisam, A. W.; Mimi Sakinah, A. M.; L., Singh (IOP Publishing, 2020)
Application of electroactive extremophiles as a biocatalytic agent inside microbial electrochemical systems (MES) holds promises for worldwide practical implementation with improved/enhanced performance under extreme environmental conditions. The MES are microbe catalysed electrochemical platforms that can turn the chemical energy stored inside organic resources/wastewater into electrical energy or other valuable bioelectrofuels with/or without an external electrical stimuli to achieve maximal oxidation of organics (by exoelectrogens) at anode and to extracellularly donating the released electrons to cathode to available electron acceptors like CO2 (by electrotrophs) to further metabolize into bioelectrofuels / or chemical compounds. The functional versatility and diverse applicability of extremophiles is due to their ability to successfully utilize various organic sources even under extreme environmental conditions. Till date, numerous efforts have been made to unravel the hidden potential of microbes in MES operating at standard environmental conditions, but its operability at extreme conditions are often overlooked. The hidden potential of extremophilic microorganisms can be channelized in MES (which either extracted from natural extreme ecosystems or cultivated in fabricated extreme biosystems) to open unknown avenues by producing novel products. This review discusses the recent state of art of extremophilic microbes by exploring novel possibilities for its application as a catalyst in MES.